2001
DOI: 10.1006/gcen.2001.7703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone and Cortisol on Na+–K+–2Cl− Cotransporter Localization and Abundance in the Gills of Atlantic Salmon

Abstract: The hormones responsible for the regulation of the teleostean gill Na ؉ -K ؉ -2Cl ؊ cotransporter have not been elucidated. With Western blotting and immunocytochemistry, Na ؉ -K ؉ -2Cl ؊ cotransporter abundance and localization were examined in the gills of Atlantic salmon (Salmo salar) following 2-week treatment with growth hormone (GH; 5.0 g ⅐ g ؊1 ), cortisol (50 g ⅐ g ؊1 ), and both hormones in combination (GH؉cortisol). GH and cortisol treatments increased gill Na ؉ -K ؉ -2Cl ؊ cotransporter abundance ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 42 publications
1
74
0
Order By: Relevance
“…Previously, cortisol stimulated NKCC mRNA in FW gill in vitro (Tipsmark et al 2002) and NKCC protein level in vivo (Pelis & McCormick 2001). A reason for the disparity in response to cortisol in the FW gill may be found in seasonal variation of sensitivity of the gill, since post-smolt salmon were used in this study whereas Tipsmark et al (2002) Scott et al (2005), where neither RU486 nor spironolactone implants affected the suppression of NKCC mRNA levels in BW-to FW-transferred killifish (Scott et al 2005).…”
Section: Cortisol Receptor Cortisol Receptormentioning
confidence: 75%
“…Previously, cortisol stimulated NKCC mRNA in FW gill in vitro (Tipsmark et al 2002) and NKCC protein level in vivo (Pelis & McCormick 2001). A reason for the disparity in response to cortisol in the FW gill may be found in seasonal variation of sensitivity of the gill, since post-smolt salmon were used in this study whereas Tipsmark et al (2002) Scott et al (2005), where neither RU486 nor spironolactone implants affected the suppression of NKCC mRNA levels in BW-to FW-transferred killifish (Scott et al 2005).…”
Section: Cortisol Receptor Cortisol Receptormentioning
confidence: 75%
“…Cortisol is the first and most important hormone that stimulates Na + , K + -ATPase activity (Pickford et al, 1970). An increase in gill Na + , K + -ATPase activity in response to cortisol treatment was previously reported in different species (Oncorhynchus mykiss [Shrimpton and McCormick, 1999]; Salmo trutta [Seidelin et al, 1999]; Anguilla japonica [Wong and Chan, 2001]; Salmo salar [Pelis and McCormick, 2001]; Sparus aurata [Mancera et al, 2002]). Some other observations also showed that exogenous cortisol can stimulate Na + , K + -ATPase activity and mitochondrion content of the ionocytes and ionocyte distribution in the gill epithelium of freshwater and seawater-adapted fishes (Laurent and Perry, 1990;Madsen, 1990b;McCormick, 1990;Seidelin et al, 1999).…”
Section: Nkcc Gene Expressionmentioning
confidence: 61%
“…Na + is transported through a paracellular pathway down its electrical gradient (McCormick, 1990). This mechanism showed that every change in Na + , K + -ATPase activity and abundance can be affected by NKCC cotransporter (Pelis and McCormick, 2001). Increasing NKCC gene expression after acclimation to salinity was previously reported in Anguilla japonica (Tse and Wong, 2006), Dicentrarchus labrax (acclimated to 36 ppt salinity) (Lorin-Nebel et al, 2006), Anguilla Anguilla and Fundulus heteroclitus (acclimated to 35 ppt salinity) (Scott et al, 2004;Scott and Schulte, 2005).…”
Section: Nkcc Gene Expressionmentioning
confidence: 74%
See 2 more Smart Citations